Can Demand for Toilets be Encouraged? Evidence from Indonesia - World Bank (Washington, DC, 2014)
In Indonesia, the World Bank worked with the government to develop new approaches to discourage open defecation and increase the number of toilets in poor, rural areas. An impact evaluation of a program to foster demand for toilets by raising awareness (instead of building sanitation facilities and hoping people would use them) showed a boost in toilet construction and a drop in diarrheal illness. Proper sanitation reduces the spread of illnesses such as diarrhea and typhoid, which can be transmitted through fecal matter. In countries where people practice open defecation in rivers, fields and forests, these illnesses are harder to stop. Fecal matter is tracked into homes and into food, causing life threatening disease, particularly among infants and children under the age of five. Development practitioners and policymakers seeking to improve sanitation and reduce open defecation are still searching for the most effective programs. Financial constraints, inadequate water systems and habit of behavior all play a role in slowing the end of open defecation. This Evidence to Policy note was jointly produced by the World Bank Group, the Strategic Impact Evaluation Fund (SIEF), and the British government's Department for International Development.